The Role of Transformational Leadership in Improving the Quality of Human Resources in Islamic Boarding Schools - Agus R., Abu Hasan; Kamil, Hafilul Fajrul (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study explores the role of transformational leadership in enhancing human resource quality at the PPIQ Nurul Jadid Quran Tahfidzul Institution, focusing on competence, professionalism, and morality. Using a qualitative case study approach, data were collected through observations, interviews, and internal documents such as training reports and work programs. Informants included deputy directors, regional heads, and teaching staff. Findings indicate that transformational leadership at PPIQ is implemented through a clear vision, student empowerment, motivational and character development, and the creation of a supportive environment. These strategies contribute significantly to building a productive educational culture and achieving the institution's vision of producing superior Quranic generations. The study offers practical insights for leadership development in religious education contexts.